Solubility of U(VI) in chloride solutions. II. The stable oxides/hydroxides in alkaline KCl solutions: Thermodynamic description and relevance in cementitious systems. (November 2018) - Çevirim-Papaioannou, Neşe; Yalçıntaş, Ezgi; Gaona, Xavier; Altmaier, Marcus; Geckeis, Horst
Abstract: The solubility of U(VI) is investigated from undersaturation conditions in 0.1, 0.51, 1.03, 3.31 and 4.58 m KCl–KOH solutions at pHm  = 7.5–14.6 (with pHm  = –log [H + ] in molal units). All experiments were performed under Ar atmosphere at T = (22 ± 2)°C. XRD, quantitative chemical analysis, SEM–EDS and TG–DTA confirm that K2 U2 O7 ·1.5H2 O(cr) is the solid phase controlling the solubility in all evaluated systems at pHm  ≥ 9.5. Below this pHm and with decreasing KCl concentration, the formation of sub-stoichiometric phases with K:U < 1 is indicated by XRD and solubility data. The concentration of uranium in equilibrium with K2 U2 O7 ·1.5H2 O(cr) shows a pH-independent behaviour up to pHm  ≈ 11 regardless of ionic strength, whereas an increase of the solubility with a well–defined slope of +1 (log [U] vs. pHm ) is observed at pHm  ≥ 11. These results are consistent with the predominance of UO2 (OH)3 – and UO2 (OH)4 2− species as previously reported in the literature. The combination of solubility data obtained in the present study with K2 U2 O7 ·1.5H2 O(cr) and the U(VI) hydrolysis scheme reported in Altmaier et al. (2017) yields a solubility product of log ∗ K °s, 0 {0.5K2 U2 O7 ·1.5H2 O(cr)} = (12.0 ± 0.2). SIT ion interaction coefficients for UO2 (OH)3 – and UO2 (OH)4 2− with K + are derived based on the newly generated experimental data in dilute to concentrated KCl systems and analogy with NaCl systems. This work extends the thermodynamic database available for U(VI) and allows more accurate source term calculations in the context of nuclear waste disposal under boundary conditions where significant K concentrations may be present and redox conditions lie in the stability field of U(VI). The K2 U2 O7 ·1.5H2 O(cr) solid phase can be considered to control the solubility of U(VI) in the degradation phase I of cement and cementitious materials. Highlights: Systematic solubility study with U(VI) in dilute to concentrated KCl systems. K2 U2 O7 ·1.5H2 O(cr) controls the solubility of U(VI) above pHm  ≈ 9.5. Comprehensive thermodynamic, chemical and SIT activity models derived. Accurate description of the UO2 2+ –H + –K + –Na + –Cl – –OH – –H2 O(l) system provided. K2 U2 O7 ·1.5H2 O(cr) postulated as relevant U(VI) phase in cement degradation stage I.